Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsami.8b10449
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density Optimization and the Anisotropic Thermoelectric Properties of Ti Self-Intercalated Ti1+xS2 Compounds

Abstract: Polycrystalline TiS (0.111 ≤ x ≤ 0.161) with high density and controllable composition were successfully prepared using solid-state reaction combined with plasma-activated sintering. TiS showed strong (00 l) preferred orientation with Lotgering factor of 0.32-0.60 perpendicular to the pressing direction (⊥), whereas the preferred orientation was not obvious along the pressing direction (∥). This structural anisotropy resulted in distinct anisotropic thermoelectric transport properties in TiS. At 300 K, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
(184 reference statements)
6
24
0
Order By: Relevance
“…On the contrary, we did not observe any preferred orientations along the //P direction. The calculation of the orientation factor LF indicated that 38 the LF factor of the sintered bulk ZrTe 5 reaches a significant value of 0.13 along the (041) plane. The scanning electron microscopy (SEM) fractured surface morphologies verified the microscopic crystalline orientation, as depicted in Figure 2d−f.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the contrary, we did not observe any preferred orientations along the //P direction. The calculation of the orientation factor LF indicated that 38 the LF factor of the sintered bulk ZrTe 5 reaches a significant value of 0.13 along the (041) plane. The scanning electron microscopy (SEM) fractured surface morphologies verified the microscopic crystalline orientation, as depicted in Figure 2d−f.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, Aoki et al 15 applied a centrifugal heating method for sintering (SnS) 1.2 (TiS 2 ) 2 , which only promoted the LF value from 0.085 to 0.13 with the centrifugal acceleration increased from 1000 to 8000 g. Sever et al 14 obtained TiS 2 bulk samples with LF ∼ 0.64 by pulsed electric current sintering (PECS) under a high pressure of 200 MPa; however, the high sintering temperature of 800 °C could have led to an obvious loss of sulfur. Besides, Tang et al 13 prepared Ti-selfintercalated Ti 1+x S 2 bulks with LF ∼ 0.6 sintered using a plasma-activated process, but it seemed to be readily affected by the intercalation amount, which is difficult to control precisely. By contrast, as can be seen from the similar high LF values for our pulverization samples, the powder pretreatment of shear pulverization processing we demonstrate here exhibits itself as a very reliable and simple technique for achieving high texturing for TiS 2 bulks.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an intercalation phase diagram that correlates the density and spatial distribution of intercalation atoms with mesoscopic properties of the intercalated compound is currently lacking. Compared with foreign atom intercalation, intercalation of a TMD by its native metal atoms has so far received scant attention 11,29,30 . Such self-intercalated TMD compounds may exist as local energy minima in the part of the phase diagram where a metal-rich stoichiometry is promoted by growth conditions using high chemical potential of metal atoms.…”
Section: Introductionmentioning
confidence: 99%